2017
DOI: 10.1108/sc-06-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Roma inclusion post Brexit: a challenge to existing rhetoric?

Abstract: Purpose of this paper: This paper proposes that the UK's exit from the EU is unlikely to impact heavily on the lived reality of Roma, given its negligible impact prior to Brexit. The paper sets out a critique of existing EU approaches to anti-Gypsyism that are based in discourses of racism and anti-nomadism and are typified in the EU hate crime agenda. The paper argues for recognition of the systemic social harms caused by discrimination against Roma in the EU and the commonality of their experience with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The authors of this paper have suggested that what is problematic about ethnic-inclusive and post-racial policies is that they both fail to recognise the context of GTR communities and their specificity of experiences. Neo-liberal economies create and perpetuate social exclusion and the systemic nature of racism and anti-gypsyism is enacted through pre-existing social structures (James and Smith, 2017). In essence, this can be seen as part of the wider systemic violence created by neo-liberal economies (Žižek, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this paper have suggested that what is problematic about ethnic-inclusive and post-racial policies is that they both fail to recognise the context of GTR communities and their specificity of experiences. Neo-liberal economies create and perpetuate social exclusion and the systemic nature of racism and anti-gypsyism is enacted through pre-existing social structures (James and Smith, 2017). In essence, this can be seen as part of the wider systemic violence created by neo-liberal economies (Žižek, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it has been suggested that Brexit will only have a limited impact on policy formulation and objectives towards Roma migrants in the UK firstly because of the desultory response by the government to Roma integration and lack of commitment to improving the position of GTR communities to date. Secondly because economic injustice, inequality and exclusion is inherent within the current socioeconomic system regardless, meaning Brexit is unlikely to create much change for the Roma living in the UK (James and Smith, 2017). Much depends on the outcome of internal divisions within both of the major political parties about Brexit and the future direction of the UK, the post-Brexit migration system and the outcome of ongoing negotiations with the EU concerning Brexit and the UK's future relationship with the EU.…”
Section: Footnote: Thinking About Brexitmentioning
confidence: 99%
“…Within the European policy environment lobbying by civil society organizations led to comprehensive EU-wide level policies for Roma 6 inclusion that was intended to guide states towards effective inclusionary policy and practice. However, the capacity of these policies to be impactful on the lived experience of Gypsies and Travellers has been questioned (James and Smith, 2017) and UK implementation of the EU Framework for Roma Inclusion has been ‘exceptionally slow’ (National Federation of Gypsy Liaison Groups et al, 2014: 13). In addition, the United Nations International Convention on the Elimination of All Forms of Racial Discrimination periodic report (2016: 6) found that Gypsies, Travellers and Roma in the UK ‘continue to face exclusion and discrimination’.…”
Section: The ‘Problem’ Of Gypsies and Travellersmentioning
confidence: 99%
“…Indeed, the acknowledgement of Gypsies and Travellers as marginalized communities has imbued contemporary reports and policy documents as noted above (and see, for example, Cemlyn et al, 2009; Lammy, 2017). The implementation of policies for Gypsy and Traveller inclusion has been slower in materializing, however (James and Smith, 2017), similar to the slow implementation of hate crime legislation generally (Mason, 2015). At the same time, the criminalization of Gypsies and Travellers continues unabated, as evidenced in the failure of local authorities to provide accommodation to Gypsies and Travellers at the same time as the Home Office announcement of proposed new powers for police to ‘crack down on illegal traveller sites’ ( sic ) (Home Office, 2019).…”
Section: The Harms Of Hatementioning
confidence: 99%
“…As is evident from this brief introduction, there has been political will to challenge the exclusion of Gypsy, Traveller and Roma communities at the macro-level of European government and at the micro-level of grass roots change-makers from civil society organisations. This has not been translated successfully however within the nation states that make up the European Union (James and Smith, 2017). Hate crime statistics and reports identify Gypsies, Travellers and Roma as experiencing high levels of victimisation on the basis of their identity (European Union Minorities and Discrimination Survey, 2012, OSCE, 2012, 2011 alongside extremely poor outcomes in relation to health, education and welfare (Brearley, 2001;Wilkin et al, 2010;Frazer and Marlier, 2011;Greenfields and Brindley, 2016).…”
Section: Introductionmentioning
confidence: 99%